Percutaneous Closure of a Large Ascending Aortic Pseudoaneurysm - Afonso Nogueira, M (2017)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2017-09-15T15:00:40Z No. of bitstreams: 1 RPC 2016 119.e1.pdf: 1012256 bytes, checksum: 92ca9742dde481909a47d01ef4aae564 (MD5)